Three new imidazole dicarboxylate metal compounds: Synthesis, structures, and magnetic property. Issue 4 (3rd April 2017) - Zhou, Rui-Sha; Shao, Jia; Li, Yang; Song, Jiang-Feng
ABSTRACT: Three new imidazole-based dicarboxylate metal compounds, Ni(HMIDC)(bpp)n (1 ), [Ni4 (HEIDC)4 (H2 O)8 ]·H2 On (2 ), and Co3 (EIDC)2 (py)2 (H2 O)2 n (3 ) have been synthesized and characterized by elemental analyses, IR, thermogravimetric analysis (TGA), and single-crystal X-ray diffraction (H3 MIDC = 2-methyl-1H-imidazole-4, 5-dicarboxylic acid; H3 EIDC = 2-ethyl-1H-imidazole-4, 5-dicarboxylic acid; bpp = 1, 3-bis(4-pyridyl)-propane; py = pyridine). Compounds1–3 show rich structural chemistry ranging from zero-dimensional, one-dimensional to two-dimensional structures. The Ni(II) centers were connected into a 1D chain in compound1 . Compound2 is a tetranuclear Ni(II) cluster. In compound3, MIDC 3− coordinates to metal centers to form a 2D honeycomb-like layer. Variable-temperature magnetic susceptibility measurements indicate antiferromagnetic interactions between cobalt centers in compound3 .